2020
DOI: 10.1155/2020/8832694
|View full text |Cite
|
Sign up to set email alerts
|

Transcutaneous Electrical Acupoint Stimulation in Early Life Changes Synaptic Plasticity and Improves Symptoms in a Valproic Acid-Induced Rat Model of Autism

Abstract: Autism spectrum disorder (ASD) is a developmental disorder characterized by social behavior deficit in childhood without satisfactory medical intervention. Transcutaneous electrical acupoint stimulation (TEAS) is a noninvasive technique derived from acupuncture and has been shown to have similar therapeutic effects in many diseases. Valproic acid- (VPA-) induced ASD is a known model of ASD in rats. The therapeutic efficacy of TEAS was evaluated in the VPA model of ASD in the present study. The offspring of a V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 61 publications
3
12
0
Order By: Relevance
“…This difference in weight gain persisted until PND21 in both exposed groups compared to controls (Figure 2A, control: 47.4 ± 0.99 g, α-HBCDD: 41.5 ± 0.56 g and VPA: 43.7 ±1.43 g). This is consistent with other studies conducted on VPA exposure, where a decrease in rat weight was highlighted at weaning age and after [27,32,33]. Lower body weight in the males after exposure to HBCDD was also reported at weaning and later [21,30].…”
Section: Effects Of α-Hbcdd and Vpa Exposure On Male Offspring Weightsupporting
confidence: 92%
See 1 more Smart Citation
“…This difference in weight gain persisted until PND21 in both exposed groups compared to controls (Figure 2A, control: 47.4 ± 0.99 g, α-HBCDD: 41.5 ± 0.56 g and VPA: 43.7 ±1.43 g). This is consistent with other studies conducted on VPA exposure, where a decrease in rat weight was highlighted at weaning age and after [27,32,33]. Lower body weight in the males after exposure to HBCDD was also reported at weaning and later [21,30].…”
Section: Effects Of α-Hbcdd and Vpa Exposure On Male Offspring Weightsupporting
confidence: 92%
“…This slowdown was observed at PND6 for the α-HBCDD group (−10%) compared to controls (p < 0.001), whereas it appeared only at PND14 for the VPA group (−8%) compared to controls (p < 0.05). For the VPA-exposed group, several studies revealed a decrease in body weight of the VPA-exposed animals compared to the controls, which was reproduced in the present results [27,31,32]. Concerning α-HBCDD, Maurice et al [21] also monitored the weight gain of pups perinatally exposed to α-HBCDD and showed retarded weight gain over the first 4 weeks of life, whereas Miller-Rhodes et al [29] did not find any differences.…”
Section: Effects Of α-Hbcdd and Vpa Exposure On Male Offspring Weightsupporting
confidence: 85%
“…As a new acupuncture technique, TEAS can simultaneously exert electrical and acupoint stimulation to promote the alleviation and relief of fatigue symptoms. [35][36][37] The selected acupoint combination in this study can regulate regulate the vitality to direct the qi, replenish qi to invigorate the spleen, and tonify the kidney to arrest spontaneous emission. Baihui, an acupoint on Du channel and confluence of all yang-channels, can clear dizziness and blurred vision and invigorate the brain and vitality; coupled with Taiyang, Shenmen, and Neiguan, it has a spirit-quieting and mind-stabilizing effects; Guanyuan is a confluent acupoint of the Ren channel and three yin channels of foot and, when coupled with Qihai and Dazhui, can reinforce vital energy, nourish yang and enrich essence; Zusanli is a lower confluent acupoint under the stomach and Sanyinjiao is a confluent acupoint of three yin channels of foot.…”
Section: Discussionmentioning
confidence: 99%
“…Although TEN has not been used in ASD, the related technique of transcutaneous electrical acupoint stimulation was found to improve anxiety, general ASD and sensory symptoms in two controlled studies, with one study demonstrating improvement in plasma arginine-vasopressin levels [50,51]. Similarly, this technique has been shown to improve behaviors in valproic acid rodent models of ASD [52]. Interestingly, there is significant interest for the use of TEN in ASD [53].…”
Section: Ten May Be An Excellent Treatment For Anxiety and Sleep In Asdmentioning
confidence: 99%